The Effect Of Baby Massage Using Lavender Essential Oil On Infant Sleep Quality At Tpmb Sumartini In 2026 - Nova Rati Lova; Rositta Febriana; Triya Puspitarati; Suparmi (International Journal of Health and Pharmaceutical (IJHP), 2026)
Infancy is a golden period of growth and development that requires special attention, including the fulfillment of quality sleep needs. Sleep disturbance in infants remains a fairly prevalent problem, both globally and in Indonesia, and can affect infants' emotions, physical growth, and cognitive development. One of non-pharmacological effort to address this sleep disturbance is baby massage combined with lavender essential oil, because of its relaxing and calming effects. This study aimed to determine the effect of baby massage using lavender essential oil on infant sleep quality at TPMB Sumartini in 2026. The design of the research is use Pre-experimental with one-group pretest-posttest design was used, involving 60 infants aged 3-12 months as the sample. Data were collected through a questionnaire before and after the baby massage intervention using lavender essential oil, then analyzed using the Wilcoxon Signed Rank Test with a total sampling technique. The results showed that before the intervention, most infants had poor sleep quality (86.7%), while after being given baby massage using lavender essential oil, infant sleep quality improved to the good category (93.3%). The statistical test showed a p-value = 0.042, meaning there is a significant effect of baby massage using lavender essential oil on infant sleep quality. This study concludes that baby massage with lavender essential oil is effective in improving infant sleep quality, so it can be used as a safe complementary midwifery care alternative that is easy for parents to apply at home.